Analisis Pemetaan Atribut Soft skills yang di siapkan oleh Lembaga Fakultas Ekonomi Universitas Negeri Padang dan yang di Butuhkan Dunia Usaha dan Industri di Sumatera Barat - Salatil Zuhra; Armida S (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the mapping of attriutes of soft skills prepared by the Institute of Economics at the State University of Padang with what is needed by the Business and Industry World in Padang that accepts students of the Faculty of Economics, State University of Padang to do an internship. This research method is descriptive qualitative. The study was conducted using a purposive sampling technique as for sources and several key informants through the results of questionnaires and in-depth interveiws or in-depth interviews directly to teh object of research. To test the validity of the data triangulation techniques are used. Based on information from this research informant, it can be explained that the soft skills atrributes needed by the business and industry world in Padang City consist: 1) initiative 2) work in teams 3) ethics/integrity 4) reliable 5) time management. These five attributes are very much needed by the business and industrial world focuses more on these city of Padang, but even though the business and industrial world focuses more on these five attributes, it does not mean that other soft skills attributes are not needed. There are several attributes of soft skills that have not ben prepared by the UNP Faculty of Economics institutions which are demands from the business and industrial world, including: 1) reliable 2) time management 3) commitment 4) self-management 5) enthusiasm 6) solving problems 7) can overcome stress 8) independent 9) motivation 10)tough 11) willingness to learn 12) cooperating 13) flexible 14) listening 15) analytical skills 16) critical thinking 17) can summarize, and 18) logically argue. The 18 attributes have not been prepared by the Faculty of Economics Institute, UNP.Keywords: bussiness and industrial world, soft skills